1 A novel recruitment method for a study of recently bereaved people in the community. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Thiemann, Pia; Newman, Rhiannon; Swash, Brooke; Price, Annabel; Fraser, Derek; Barclay, Stephen
Abstract : Background: NICE guidelines state that 'everyone should be given bereavement support according to their needs and preferences'. The few existing studies on the bereaved persons perspective of Primary Care bereavement support are often limited by recruitment biases, low participant numbers and recall bias. We assessed the feasibility and acceptability of a new recruitment method for recently bereaved people in the community. Methods: Recently bereaved people were invited to take part in a questionnaire study when registering a death. Registry Officers handed out study packs over a 12 week period. On receipt of reply slip indicating interest in participation, participants were sent further study information and after 6 weeks a postal questionnaire concerning bereavement support. Questionnaires could also be completed online. Qualitative interviews with a subsample of Registry Officers (n=6) and bereaved people (n=14) investigated their views of the recruitment approach. Results: Between 25/07/2016 and 14/10/2016, 1726 deaths were registered and 1069 study packs were distributed: 72 reply slips and 6 online-questionnaires were returned (response rate 7%). Over 50% of reply slips were returned within a week of registering the death. The questionnaire response rate was 83% (60/72). Interviews highlighted that the bereaved and Registry Officers felt comfortable with the study recruitment approach. Data on reasons for refusal, collected from Registry Officers and reply slips declining participation did not reveal ethical concerns or distress caused by the recruitment approach. Conclusions: The response rate was lower than previous bereavement studies, possibly related to the early timing of recruitment. Nevertheless, novel data were obtained from early in bereavement and the recruitment timing was found to be acceptable by all consulted participants. We conclude that a sensitive recruitment approach even shortly after the death can be acceptable to the (newly) bereaved, although the low response rate calls into question the feasibility of the Registry Officers approach.